First phytochemical study and biological activity of the leaves ethanolic extract from Cissus spinosa Cambess - Sinhorin, Adilson Paulo; Godoy, Bruna Serpa de Almeida; Sinhorin, Valéria Dornelles Gindri; Castoldi, Lindsey; Sugui, Marina Mariko; Bicudo, Rogério de Campos (Scientia Medica, 2020)
Aims: The objective of this study was to identify the phytochemical profile and to evaluate the biological effects of the crude ethanolic extract (EE) and the ethanolic fraction (EF) of leaves of the species Cissus spinosa Cambess, after oxidative stress induced by cyclophosphamide (CP) in mice. Methods: Phytochemical profile was performed detecting functional groups and, analysis of total flavonoids and phenols concentration, as well as the antiradical activity in EE and EF. The phytochemical characterization was done for the identification of flavonoids present in the leaves of the plant. In the biochemical tests, hematological parameters, glucose, total cholesterol, creatinine, alkaline phosphatase and aminotransferases dosages in plasma, enzymatic and non-enzymatic antioxidants and lipid damage marker were evaluated in different tissues (liver, kidney and heart), besides genotoxic and immunological analyzes. The animals received 15 days of treatment, via gavage, with EE (50 mg kg-1) or EF (50 mg kg-1) and on the 15th day, an intraperitoneal injection of CP (100 mg kg-1) or saline (0.9%). After 24 h the last treatment, the animals were anesthetized for blood withdrawal, sacrificed and removal of the organs. Results: In the phytochemical analyzes, the presence of alkaloids, flavonoids and phenols was identified, the latter presented a higher concentration for EF. Eight flavonoids were identified - Rutin, Quercetin-3-β-D-glucoside, Quercitrin, Taxifolin, Quercetin, Canferol, Luteolin and Apigenin. In the biochemical analyzes, in general, EE showed a better antioxidant action against oxidative damages, hypoglycemic and antitilipemic action when comparing with EF, probably due to the synergism caused by flavonoids. It was observed the reduction and an increase of micronucleated polychromatic erythrocytes, due to the action of antioxidant compounds and alkaloids present in the plant, also considering the question of the seasonal period that directly interferes in the production of these compounds. In the immunological analysis, the extracts did not stimulate the spontaneous production of oxygen peroxide (H2O2) and nitric oxide (NO•). Conclusions: Other studies, such as the variation of the chemical composition of the plant by local seasonality, hypoglycemic and antilipemic action, should be carried out to better delineate the biological action present in this plant. ***Primeiro estudo fitoquímico e atividade biológica do extrato etanólico de folhas de Cissus spinosa Cambess*** Objetivos: O objetivo deste estudo foi identificar o perfil fitoquímico e avaliar os efeitos biológicos do extrato etanólico bruto (EE) e da fração etanólica (EF) das folhas da espécie Cissus spinosa Cambess, após estresse oxidativo induzido pela ciclofosfamida. (CP) em camundongos. Métodos: O perfil fitoquímico foi realizado detectando grupos funcionais e, análise da concentração de flavonoides e fenóis totais, bem como a atividade antirradical em EE e EF. A caracterização fitoquímica foi realizada para a identificação de flavonoides presentes nas folhas da planta. Nos testes bioquímicos, os parâmetros hematológicos, as dosagens de glicose, colesterol total, creatinina, fosfatase alcalina e aminotransferases no plasma, os antioxidantes enzimáticos e não enzimáticos e o marcador de dano lipídico foram avaliados em diferentes tecidos (fígado, rim e coração), além de análises genotóxicas e imunológicas. Os animais receberam 15 dias de tratamento, via gavagem, com EE (50 mg kg-1) ou EF (50 mg kg-1) e no 15º dia, injeção intraperitoneal de CP (100 mg kg-1) ou soro fisiológico (0,9%) . Após 24 h do último tratamento, os animais foram anestesiados para retirada do sangue, sacrificados e após a retirada dos órgãos. Resultados: Nas análises fitoquímicas, identificou-se a presença de alcaloides, flavonoides e fenóis, estes últimos apresentaram maior concentração para EF. Oito flavonoides foram identificados - rutina, quercetina-3-β-D-glicosídeo, quercitrina, taxifolina, quercetina, canferol, luteolina e apigenina. Nas análises bioquímicas, em geral, o EE apresentou melhor ação antioxidante contra os danos oxidativos, ação hipoglicemiante e antitilipêmica quando comparada à EF, provavelmente devido ao sinergismo causado pelos flavonoides. Observou-se a redução e um aumento de eritrócitos policromáticos micronucleados, devido à ação de compostos antioxidantes e alcaloides presentes na planta, considerando também a questão do período sazonal que interfere diretamente na produção desses compostos. Na análise imunológica, os extratos não estimularam a produção espontânea de peróxido de oxigênio (H2O2) e óxido nítrico (NO•). Conclusões: Outros estudos, como a variação da composição química da planta por sazonalidade local, ação hipoglicemiante e antilipêmica, devem ser realizados para melhor delineamento da ação biológica presente nesta planta. Palavras-chave: antioxidante; Cissus; estresse oxidativo; flavonoides; genotoxicidade; imunomodulação.